Preliminary checklist of marine invertebrate fauna within the intertidal of Teluk Penyabong and Teluk Gorek, Mersing, Johor, Malaysia - Cob, Z.C; Samat, A.; Muda, W.M.L.W.; Mazlan, A.G. (University Kebangsaan Malaysia, 2012)
Study on the biodiversity and distribution of marine invertebrate fauna within the intertidal areas of Teluk Penyabung and Teluk Gorek, Mersing has been conducted from July 4th to 9th, 2010. Field sampling was carried out using a transect line method, during the low tide period. The transect line was laid down along the tidal height, perpendicularly to the shoreline. All marine invertebrates encountered within 1 m areas of the line were recorded. Species that could not be identified on site were taken and preserved in 5% formalin for further analysis and identification. Results showed that mollusk was the most dominant phyla, followed by the crustaceans and other organisms. Among the mollusks, the Littorinidae, Neritidae, Muricidae and Patellidae was the most common and can be found in all stations. Within the crustaceans the fiddler crab (Ocypodidae) and tree climbing crab (Sesarmidae) was the most common. In areas with hard substrates, the acorn barnacles (Chthamalidae) were also found abundant. In this paper the biodiversity and distributional pattern of marine invertebrate fauna within the intertidal areas of the study sites were documented and discussed.